Interaction of the p.Q141K Variant of the ABCG2 Gene with Clinical Data and Cytokine Levels in Primary Hyperuricemia and Gout - Horváthová, Veronika; Bohatá, Jana; Pavlíková, Markéta; Pavelcová, Kateřina; Pavelka, Karel; Šenolt, Ladislav; Stibůrková, Blanka (Journal of clinical medicine, 2019)
Gout is an inflammatory arthritis influenced by environmental risk factors and genetic variants. The common dysfunctional p.Q141K allele of the ABCG2 gene affects gout development. We sought after the possible association between the p.Q141K variant and gout risk factors, biochemical, and clinical determinants in hyperuricemic, gouty, and acute gouty arthritis cohorts. Further, we studied the correlation of p.Q141K allele and levels of pro-/anti-inflammatory cytokines. Coding regions of the ABCG2 gene were analyzed in 70 primary hyperuricemic, 182 gout patients, and 132 normouricemic individuals. Their genotypes were compared with demographic and clinical parameters. Plasma levels of 27 cytokines were determined using a human multiplex cytokine assay. The p.Q141K variant was observed in younger hyperuricemic/gout individuals (p = 0.0003), which was associated with earlier disease onset (p = 0.004), trend toward lower BMI (p = 0.056), and C-reactive protein (CRP, p = 0.007) but a higher glomerular filtration rate (GFR, p = 0.035). Levels of 19 cytokines were higher, mainly in patients with acute gouty arthritis (p < 0.001), irrespective of the presence of the p.Q141K variant. The p.Q141K variant influences the age of onset of primary hyperuricemia or gout and other disease-linked risk factors and symptoms. There was no association with cytokine levels in the circulation.
Keywords: p.Q141K; acute gouty arthritis; cytokines; hyperuricemia; gout; ABCG2